(untitled) (Herald of Journalism, 2018)
This article represents the results of the research “Options of using the local word “uyatmen” in the media texts. Applying the content-analysis and descriptive method, the author groups six categories of effective practical application of the neologism in journalistic works. A number of conclusions were drawn: the word “uyatmen” is widely used in modern print and electronic kazakhstani media in various genres; it is used as common and own name, in the singular and plural; it is given with a synonym or antonym, as well as in the composition of the phrase and in rhetorical question; the word passed the stage of socialization and entered the stage of lexicalization; the concept was fixed in the national cognitive base and linguistic space of Kazakhstan people, largely due to the media. Key words: mass media, text, localism, uyatmen.